2022
DOI: 10.3390/ijms23158827
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Myeloid Neoplasms

Abstract: Myeloid neoplasms arise from malignant primitive cells, which exhibit growth advantage within the bone marrow microenvironment (BMM). The interaction between these malignant cells and BMM cells is critical for the progression of these diseases. Extracellular vesicles (EVs) are lipid bound vesicles secreted into the extracellular space and involved in intercellular communication. Recent studies have described RNA and protein alterations in EVs isolated from myeloid neoplasm patients compared to healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…Finally, the active complex interacts with the 3′-UTR of target mRNA through complementary pairing of base pairings, causing translational repression or RNA degradation (Figure 1A). 83−85 Through this process, miRNAs were involved in a series of cellular processes, including apoptosis, 4−6 oxidative stress, 7 cell proliferation, 8,9 inflammation, 10,11 hematopoiesis, 4,12 and tumorigenesis. 13,14 Recent studies revealed that miRNAs not only have an intracellular function but also stably exist in biological fluids such as saliva, cerebrospinal fluid, plasma, serum, gingival fluid, and urine.…”
Section: Micrornasmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the active complex interacts with the 3′-UTR of target mRNA through complementary pairing of base pairings, causing translational repression or RNA degradation (Figure 1A). 83−85 Through this process, miRNAs were involved in a series of cellular processes, including apoptosis, 4−6 oxidative stress, 7 cell proliferation, 8,9 inflammation, 10,11 hematopoiesis, 4,12 and tumorigenesis. 13,14 Recent studies revealed that miRNAs not only have an intracellular function but also stably exist in biological fluids such as saliva, cerebrospinal fluid, plasma, serum, gingival fluid, and urine.…”
Section: Micrornasmentioning
confidence: 99%
“…These functional miRNAs form the RISC via binding to AGO. Finally, the active complex interacts with the 3′-UTR of target mRNA through complementary pairing of base pairings, causing translational repression or RNA degradation (Figure A). Through this process, miRNAs were involved in a series of cellular processes, including apoptosis, oxidative stress, cell proliferation, , inflammation, , hematopoiesis, , and tumorigenesis. , …”
Section: Micrornasmentioning
confidence: 99%
See 1 more Smart Citation